Stress e satisfação das mães em cuidados intensivos neonatais. - Gustavo Rocha; Linda Candeias; Madalena Ramos; Teresa Maia; Hercília Guimarães; Victor Viana (Acta Médica Portuguesa, 2011)
The admission and stay in a Neonatal Intensive Care Unit represents an anxious experience to parents, because of their frustrated expectations and the confrontation with the possibility of newborn's death. The aims of this study were to assess how mothers cope with physical characteristics of the context, with treatments and with the loss of the idealized parental role; to assess how mothers evaluate the medical and nurse staff performance; and to assess the degree of satisfaction with the Service.A sample of 100 mothers, whose newborns were admitted at the Neonatal Intensive Care Unit,was asked to fulfil a specific survey.In a general way, according to the mean of all stress subscales, the total experienced stress was moderate. Significant associations or differences between scholarity and stress were not found, as well as with mother's age. The loss of parental role was the most anxious factor for mothers. The satisfaction with medical team was inversely related to stress. Mothers were satisfied with nurse team performance.The loss of the idealized parental role is the most anxious experience for the mothers. The observed results highlight the need for the continuous change of the neonatal unit in a more warming environment for the mothers and their newborns.